2006
DOI: 10.2174/138161206779010549
|View full text |Cite
|
Sign up to set email alerts
|

The Redox Regulation of Thiol Dependent Signaling Pathways in Cancer

Abstract: Reactive oxygen species (ROS) play a central role as second messengers in many signal transduction pathways, where they can post-translationally modify proteins via the oxidation of redox sensitive cysteine residues. The range of cellular processes under redox regulation is extensive and includes both the proliferative and apoptotic pathways. Control of the cellular redox environment is therefore essential for normal physiological function and perturbations to this redox balance are characteristic of many path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(106 citation statements)
references
References 123 publications
1
103
0
2
Order By: Relevance
“…Refs. [43][44][45]. For instance, a transcript variant (TXNRD1_v3) of the selenoprotein thioredoxin reductase 1 encodes an atypical N-terminal Grx domain.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [43][44][45]. For instance, a transcript variant (TXNRD1_v3) of the selenoprotein thioredoxin reductase 1 encodes an atypical N-terminal Grx domain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most chemotherapeutic drugs are reported to arrest or delay cell cycle progression, and if the DNA damage or other cellular defects are extensive, the cell will undergo either apoptosis or cellular senescence (Lukas et al, 2004;Bartkova et al, 2005). Moreover, cancer cells may be considered to display an enhanced or higher level of basal stress, such as increased levels of reactive oxygen species or stress kinase activity, and it is precisely the deregulation of cell cycle checkpoints that allow cancer cells to tolerate such cellular conditions, while simultaneously promoting genomic instability and tumour progression (Giles, 2006;Wu, 2006;Fruehauf and Meyskens, 2007). One such mechanism by which cancer cells can tolerate cellular stress is the deactivation of FoxO3a, which would be anticipated to be activated by oxidative stress and stress kinases, both of which may converge through c-Jun N-terminal kinase-mediated phosphorylation of FoxO3a (Essers et al, 2004(Essers et al, , 2005Vogt et al, 2005;Huang and Tindall, 2007).…”
Section: Foxo-cell Cycle and Apoptosismentioning
confidence: 99%
“…ROS-induced mutagenesis is an early causative factor in carcinogenesis, and ROS-mediated mitogenic signaling and redox modulation of apoptotic and survival pathways contribute to malignant transformation and progression [1][2][3][4]. ROS production from mitochondrial and other sources is increased in cancer cells leading to alterations of *Address correspondence to: Georg T. Wondrak, Ph.D., University of Arizona, Arizona Cancer Center, 1515 North Campbell Avenue, Tucson, AZ 85724 USA, E-mail: E-mail: wondrak@pharmacy.arizona.edu, Telephone: 520-6269017, FAX: 520-6268567.…”
Section: Introductionmentioning
confidence: 99%
“…For example, constitutive activation of nuclear factor κB signaling in human melanoma cells occurs as a result of autocrine generation of ROS contributing to proliferative signaling and the notorious resistance of melanoma cells to induction of apoptosis by chemotherapeutic agents [8,9]. In addition to substantiating the emerging role of the cellular redox environment in the general regulation of proliferation, differentiation, and survival [10], recent research has revealed the differential redox control of proliferation and viability in nontransformed versus malignant cells [1,2,6,11]. For example, in nontransformed NIH 3T3 cells, constitutive ROS production occurs at low levels, whereas in CT26 colon and Hepa 1-6 liver tumor cells, high concentrations of ROS, close to the threshold of cytotoxicity, are produced by mitochondria.…”
Section: Introductionmentioning
confidence: 99%